The emergence of multi‐resistantEnterococcus faecalisclonal complex, CC4, causing nosocomial infections. Issue 8 (August 2018) - Dai, Dongfa; Wang, Huizhu; Xu, Xinmin; Chen, Chen; Song, Chuan; Jiang, Dong; Du, Pengcheng; Zhang, Yuanyuan; Zeng, Hui
Abstract : Purpose. : Enterococcus faecalis is commonly found as a commensal gut bacteria, but some linages have caused increasing extra‐gastrointestinal infections. In particular, strains with high‐level virulence or antimicrobial resistance are prevalent in healthcare settings as nosocomial pathogens. This study was performed to elucidate the epidemiological characteristics and antimicrobial susceptibility profiles of E. faecalis causing nosocomial infections in a Chinese general hospital over a 4‐year period. Methodology. : We collected 77 isolates causing extra‐gastrointestinal infections from patients at 14 different wards in a tertiary hospital from 2011 to 2014. The population relationship was assessed by multilocus sequence typing and multilocus variable‐number tandem repeat analysis. The Kirby‐Bauer disk diffusion method was used to evaluate susceptibility against 11 antimicrobial agents. Results. : The isolates showed high‐level resistance to tetracycline (86.5 %), erythromycin (78.4 %), rifampin (62.2 %), etc. The major clonal complexes (CCs) included CC4, CC16 and CC21. As the most dominant subtype, CC16 was identified in almost all of the wards and all types of samples, but the isolation rate decreased continually. In contrast, the isolation rates of CC4 and CC21 increased and the proportion of these two CCs in 2014 was more than three times that in 2011. In addition, CC4 showed higher resistance than CC16. Conclusions. : This study demonstrated the prevalent subtypes and resistance profiles of E. faecalis causing nosocomial infection, and indicated that CC4 may be a newly emerging high‐risk, multi‐resistant cluster. More surveillance is urgently needed, which will increase our understanding of the prevention and treatment of such infections.